Effect of short heat treatments on the microstructural evolution and hardness of thixoformed graphene reinforced aluminium composites (Kesan rawatan haba singkat terhadap evolusi mikrostruktur dan kekerasan komposit aluminium diperkuat grafen pembentukan tikso) - Wakhi Anuar, Nur Farah Bazilah; Omar, Mohd Zaidi; Salleh, Mohd Shukor; WWan Zamri, Wan Fathul Hakim; Md Ali, Afifah (Penerbit Universiti Kebangsaan Malaysia, 2024)
Aluminium metal matrix composites are increasingly being used in numerous industries due to their lightweight nature and high strength. The incorporation of graphene into aluminium metal matrix composites has garnered significant interest owing to graphene’s capacity to enhance numerous properties concurrently. Hence, this study aimed to fabricate a 0.3 wt.% graphene nanoplatelets reinforced A356 alloy (GNP-A356) composite through stir casting followed by thixoforming and short T6 heat treatment processes. It also evaluated the microstructure and mechanical properties of GNP-A356 after the thixoforming process and short T6 heat treatment. The microstructure of alloy and composite was confirmed by optical microstructure, field emission scanning electron microscopy images, and X-ray diffraction. Microstructure investigations demonstrate the impact of the stirring process on the structural transformation of the